Role Of Women Leadership Attributes In Defense Services - Nautiyal, Mayank (International Journal of Psychosocial Rehabilitation, 2019)
In certain settings, women really do better than men. Women’s participation in the military would quadruple the number of qualified candidates for sensitive positions that need people’s skills. Armed forces are better able to put their finest and most diplomatic troops to work to rapidly resolve conflicts when they have access to a larger pool of potential recruits. Restricting women from serving in combat perpetuates sexism since it is widely accepted that combat experience is a prerequisite for advancement to senior officer posts. In the military, women must be subjected to the same dangers as males if they are to be afforded the same chances.